2003
DOI: 10.1177/002215540305100109
|View full text |Cite
|
Sign up to set email alerts
|

Electron Microscopic Immunogold Localization of Salivary Mucins MG1 and MG2 in Human Submandibular and Sublingual Glands

Abstract: S U M M A R YThe human salivary mucins MG1 and MG2 are well characterized biochemically and functionally. However, there is disagreement regarding their cellular and glandular sources. The aim of this study was to define the localization and distribution of these two mucins in human salivary glands using a postembedding immunogold labeling method. Normal salivary glands obtained at surgery were fixed in 3% paraformaldehyde-0.1% glutaraldehyde and embedded in Lowicryl K4M or LR Gold resin. Thin sections were la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
2

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 30 publications
4
31
2
Order By: Relevance
“…Alternatively, the split MG2 bands could arise by expression of different glycoforms in mucous or serous acini. This is consistent with immunogold electron microscopy experiments showing that both mucous and serous acini produce MG2 [9].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Alternatively, the split MG2 bands could arise by expression of different glycoforms in mucous or serous acini. This is consistent with immunogold electron microscopy experiments showing that both mucous and serous acini produce MG2 [9].…”
Section: Discussionsupporting
confidence: 90%
“…Immunochemical and in situ hybridization studies have localized MG2 to serous acini in submandibular, sublingual, and minor salivary glands [5,6] whereas another group using the same procedures localized MG2 to a subset of mucous acini in submandibular and labial salivary glands [7,8]. On the other hand, by using immunogold electron microscopy, we found that MG2 could be localized in both mucous and serous acini of submandibular and sublingual glands, but not in parotid glands [9]. Together, the information above indicates that the MUC7 gene for MG2 has complex expression patterns in the major salivary glands.…”
Section: Introductionmentioning
confidence: 61%
“…One group localized MUC7 to serous acini in SMGs and LGs using immunohistochemistry and in situ hybridization [40,41]; whereas two other groups clearly defined mucous acini as the expression sites using the same techniques [42,43]. Furthermore, electron microscopic immunogold localization detected MUC7 in both serous and mucous cells with varying intensities [44]. Thus, the results presented here (Fig.…”
Section: Muc7 Muc19 and Fcgbp Are Predominantly Expressed In Mucousmentioning
confidence: 57%
“…Interestingly, MUC7 mucin, which is well-expressed in mucosal and serosal cells in salivary glands (205), is typically localized to a subset of serous cells in SMG, but only in 15-20% of airway tissue from normal individuals (245). Studies on MUC gene expression in tissues from patients with airway diseases are limited in number and overviewed in section II. Mucin expression in the in vitro NHBE and NHNE model cell systems has also been evaluated in cells derived from healthy airway tissues (19).…”
Section: Mucin Expression In Epithelial Tissues/cells and Airway Cmentioning
confidence: 99%